Models of Technical Progress and the Golden Rule of Research - Phelps, E. S. (Review of Economic Studies, 1966)
Journal Article Models of Technical Progress and the Golden Rule of Research Get access E. S. Phelps E. S. Phelps Yale University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 2, April 1966, Pages 133–145, https://doi.org/10.2307/2974437 Published: 01 April 1966